REFLEKSI PEMBERDAYAAN MASYARAKAT DESA HUTAN Studi Refleksi Pelaksanaan Pemberdayaan Masyarakat Desa Kawasan Hutan di KPH Padangan Kabupaten Bojonegoro - Suji, Suji (Jurnal Sosial Ekonomi Pertanian, 2010)
The research on the profile Chilli seed breeding and its delivering service was done on MayâAugust 2005 in Multi Agro Wiyata and Nuansa Agro Insani, Jember regency. The goals were to find description of service marketing perfomance and to analyce the dominant factor in service marketing from both service providers.There are seven variables in service marketing exactly: Product, Price, Promotion, Place, People, Process and Physical Evidence. This research used survey method with quitsioner by 200 farmers. Services are categorized as âmedium-high contactâ and thus a high degree of interaction. Interpersonal communication between farmers and service professional with usage appropiate technology is essential for succesful service delivery. The result of descriptive analysis showed that the diferenciation in service marketing performance between Multi Agro Wiyata and Nuansa Agro Insani are product and process delivering service. The dominant factors in service marketing,